No Evidence That Homologs of Key Circadian Clock Genes Direct Circadian Programs of Development or mRNA Abundance in Verticillium dahliae - Cascant-Lopez, Emma; Crosthwaite, Susan K.; Johnson, Louise J.; Harrison, Richard J. (Frontiers in Microbiology, 2020)
Many organisms harbour circadian clocks that promote their adaptation to the rhythmic environment. While a broad knowledge of the molecular mechanism of circadian clocks has been gained through the fungal model Neurospora crassa, little is known about circadian clocks in other fungi. N. crassa belongs to the same class as many important plant pathogens including the vascular wilt fungus Verticillium dahliae. We identified homologues of N. crassa clock proteins in V. dahliae, which showed high conservation in key protein domains. However, no evidence for an endogenous, free-running and entrainable rhythm was observed in the daily formation of conidia and microsclerotia. In N. crassa the frequency (frq) gene encodes a central clock protein expressed rhythmically and in response to light. In contrast, expression of Vdfrq is not light-regulated. Temporal gene expression profiling over 48 hours in constant darkness and temperature revealed no circadian expression of key clock genes. Furthermore, RNA-seq over a 24 h time-course revealed no robust oscillations of clock-associated transcripts in constant darkness. Comparison of gene expression between wild-type V. dahliae and a ΔVdfrq mutant showed that genes involved in metabolism, transport and redox processes are mis-regulated in the absence of Vdfrq. In addition, VdΔfrq mutants display growth defects and reduced pathogenicity in a strain dependent manner. Our data indicate that if a circadian clock exists in Verticillium, it is based on alternative mechanisms such as post-transcriptional interactions of VdFRQ and the WC proteins or the components of a FRQ-less oscillator. Alternatively, it could be that whilst the original functions of the clock proteins have been maintained, in this species the interactions that generate robust rhythmicity have been lost or are only triggered when specific environmental conditions are met. The presence of conserved clock genes in genomes should not be taken as definitive evidence of circadian function.